2017
DOI: 10.1021/acschembio.6b01066
|View full text |Cite
|
Sign up to set email alerts
|

Single Particle Observation of SV40 VP1 Polyanion-Induced Assembly Shows That Substrate Size and Structure Modulate Capsid Geometry

Abstract: Simian virus 40 capsid protein (VP1) is a unique system for studying substrate-dependent assembly of a nanoparticle. Here, we investigate a simplest case of this system where 12 VP1 pentamers and a single polyanion, e.g. RNA, form a T=1 particle. To test the roles of polyanion substrate length and structure during assembly, we characterized the assembly products with size exclusion chromatography, transmission electron microscopy, and single-particle resistive-pulse sensing. We found that 500 and 600 nt RNAs h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…SV40 favors stepwise assembly of the capsid that occur concomitantly with nucleic acid binding [56]. Consistent with our results, SV40 assembly has shown tertiary structure of the cargo and length of cargo influence the assembly of the virion [57]. Computational models show that weak CP-CP interactions favor initial formation of a disordered CP-nucleic acid oligomer that then assembles, while strong interactions favor co-assembly [19,20,21].…”
Section: Discussionsupporting
confidence: 86%
“…SV40 favors stepwise assembly of the capsid that occur concomitantly with nucleic acid binding [56]. Consistent with our results, SV40 assembly has shown tertiary structure of the cargo and length of cargo influence the assembly of the virion [57]. Computational models show that weak CP-CP interactions favor initial formation of a disordered CP-nucleic acid oligomer that then assembles, while strong interactions favor co-assembly [19,20,21].…”
Section: Discussionsupporting
confidence: 86%
“…CCMV has, for instance, a preference for packaging of polystyrene sulfonate (PSS), which favors a collapsed state over singlestranded RNA, which acts like a many-branched polymer (43). For SV40, it is shown that tertiary structure of PSS or RNA and the size of the substrate affect the assembly (19). All these experiments show that the template around which the capsid forms decisively influences assembly.…”
Section: Discussionmentioning
confidence: 99%
“…We used two protocols to obtain VP1 pentamers. Initially, we followed the procedure described by Li et al (41). Briefly, DNA-filled VLPs were dissociated by dialysis against 20 mM Tris-Cl (pH 8.9), 50 mM NaCl, 2 mM dithiothreitol (DTT), and 5 mM EDTA at 4 C. The dialysate was centrifuged to remove aggregated protein and then loaded on a Superose 6 column (GE Lifesciences, Chicago, IL) equilibrated in 100 mM 3-(N-morpholino)propanesulfonic acid (MOPS; pH 7.2), 250 mM NaCl.…”
Section: Methodsmentioning
confidence: 99%